Construcción de la realidad a través de los medios de comunicación: terrorismo islámico, intereses geopolíticos y criminalidad en la Triple Frontera del Paraná (2015)
This article examines the role played by the media in theconstruction of reality, and specifically the role played –moreclearly after the attacks of September 11, 2001 in NewYork and Virginia– by the American media –including somenewspapers, television stations, magazines, and governmentalagencies’ websites (where official documents are periodicallypublished)– and certain “alternative media” (anti-capitalist andanti-American), mainly Latin American, in the construction of theexternal image of the so-called Parana Tri-Border Area (Paraguay,Brazil, Argentina). As it will be seen, these representations –especially the American ones–, despite having little support,have contributed to produce a negative external image of thearea, almost cinematic, marked by the presence of Islamicterrorists, traffickers of all kinds of products and CIA agents, aview that seems to differ from the one that prevails within theTri-Border Area.